Pendampingan Siswa Pada Kegiatan Tahfidz Alqur’an Dengan Metode Jibril di SMPN 44 Padang: - Ruri Albersa; Martin Kustati; Nana Sepriyanti (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This assistance is carried out with the aim of making it easier for students to memorize the Al-Quran. This assistance is motivated by the fact that there are still many students lacking in reciting Al-Qur'an verses which are not in accordance with the correct recitation rules. This mentoring is to help students memorize verses of the Al-Qur'an in the Tahfidz extracurricular program, especially juz 30. The method used in this mentoring is the Participatory Action Research (PAR) strategy. The method for implementing this assistance is the Jibril Method. Jibril's method is the right method among the many methods of memorizing the Koran. Jibril's method is talqin-taqlid (imitation), students imitate their teacher's reading where the teacher's position is as a learning resource, carried out by the teacher starting to read a piece of verse then continuing with students repeating the reading read by the teacher first. The results of mentoring using the Jibril method show that: (1) Increase students' ability to memorize the Al-Qur'an. (2) Increase students' understanding in memorizing their memorization. (3) Increasing students' enthusiasm in repeating their memorization. . Keywords: Mentoring; Method Jibril; Tahfidz